7-Year experience of transcatheter aortic valve implants (TAVI) in a Western Cape private healthcare setting - Weich, Hellmuth; Liebenberg, Jacques; Van Wyk, Jacques; Vivier, Rocco; Barnard, Barry; Abelson, Mark; Phillips, Andre; Mabin, Tom (SA Heart Journal, 2019)
Introduction: We describe the largest South African transcatheter aortic valve implantation (TAVI) outcome report of a single team in the Western Cape, over a 7-year period from 2009 - 2016. Methods: All patients who received TAVI at Mediclinic Vergelegen and Mediclinic Panorama were prospectively entered into a database. A total of 244 implants (61 CoreValve and 183 Edwards valves) were performed. Results: Patients were high risk with a mean STS score of 7.89 (standard deviation (SD) 5.7) and mean logistic EuroSCORE of 26.5 (SD 12.5). There was a trend toward lower risk over time. Procedures were initially performed mainly via a transapical approach, but this changed to mostly transfemoral with the introduction of smaller delivery systems. Procedural success rate was 91.8% for CoreValve and 88.5% for Edwards cases. Mean length of hospital stay following TAVI was 9 days initially, but this declined to 4 days for the latter part of our experience. One year mortality was 19% and one year stroke rate was 10%. Conclusion: Despite the limitations of a study of this nature, our group could document outcomes similar to international studies, with improvements over time and illustrating successful cooperation between different hospitals to expand exposure and experience in a resource-constrained environment.